(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Despite advancements in treatment and care, HIV infection continues to pose significant challenges, especially in pediatric populations. Children living with HIV often experience immune dysregulation and heightened inflammatory responses, leading to increased susceptibility to opportunistic infections and disease progression. Cytokines are critical signaling molecules that orchestrate the immune response and influence the pathogenesis of HIV infection (Tudela et al., 2014). The epidemiological situation of tuberculosis in different regions of the world is constantly changing as a result of the complex relationship between population movements, the number and distribution of tuberculosis patients , the socio-economic and cultural level of the population, the availability of medical care, and the prevalence of HIV infection